Kritik Hadis Zakaria Ouzon - Baharudin Zamawi Zamawi (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2019)
Hadis has strength authority as Islamic law. It’s function is the explanatory of the Qur’an and otherwise. The significance of the hadis requires its protecting and conserving by codification. Muslim scholars had collected thousands of hadis in many books that well-known as The Nine Primary Book of Hadis (Kutub al-Tis’ah). One of them, Sahih al-Bukhari, was claimed as the most authentic book, because it is contain the only authentic (sahih) hadis. Moreover Sahih al-Bukhari had important position as the source of Islamic law right below Quran. But the popularity of Sahih al-Bukhari was underestimated by Zakaria Ouzon, the scholar who criticized works of many muslim scholars, one of them is Sahihh al-Bukhari. He claimed that hadis collected in Sahih al-Bukhari was authentic (sahih) and could be used as hujjah. He argued that some hadis in Sahih al-Bukhari must be doubted as authentic, because of its contrary to Quran and Hadis Mutawwatir textualy. Zakaria used comparative theory to proof the authenticity of hadis by comparing hadis in Sahih al-Bukhari with Quran and Hadis Mutawwatir. One of hadis’ that criticized by Zakaria was hadis about angels cursed wife who denied the husband’s invitation for having sex. He stated that this hadis was contrary to Quran and the principles of Islamic doctrine which respect the dignity and honor of the women. Therefor that hadis must be doubted its authenticity. Zakaria’s thoughts about authenticity of hadis in Sahih al-Bukhari was stated in his work, Jinayat al-Bukhari, probably, has the same tendency with most contemporary muslim scholars who tried to reconstruct the interpretation of hadis which literally contraty to Quran, hadis mutawwatir, and Islamic doctrines. But Zakaria seems to criticize loudly with doubting the authenticity of hadis in Sahih al-Bukhari.